Memória e experiência de judeus de Higienópolis e arredores, São Paulo (1960-1970) - Chermont, Lucia Ribeiro (2011)
This study is focused on the personal experience of Jews from the Higienópolis neighborhood in São Paulo and its surroundings, where the presence of the Jewish community is strong. From that start point, this project intends to comprehend, though the eyes of some of these characters, how this spatial choice was experienced, not merely as a practical choice, but also from a sentimental and imaginational point of view. With interviews, to better comprehend the subjects experiences, the attempt was to find out details of their lives, their way of life, their impressions on the trajectory of their parents and their own and their consciousness about their lives, not just politically and economically, but of all of which can be called to be part of the substance of identity and relationship lived by them. An important element in this research was the part of the Jewish traditions chosen by the subjects as relevant to live their lives by, as well as the singularity of their trajectory, the personal experience shared socially though their own choices, the way they behave toward inherited conditions, the values they live by and finally how these experiences, in this place so full of meaning and particularities, helped rebuild the ethnic-religious lives of the people in this study. Another core question in this study is to verify how this occupation occurred, from the 1960 s, and the numerous Jewish institutions that moved to the area or that chose the neighborhood as the place for their headquarters